VALIDITY OF SUPPLEMENTARY TEACHING MATERIALS ON BUFFER SOLUTION TO TRAIN ARGUMENTATION - Dyah Kirani Noviyana; Suyono (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2024)
Supplementary teaching materials are tools used as an addition to learning. Good teaching materials must pass through a feasibility assessment, such as validity. Validity is important to review the quality and content of teaching materials, by measuring the suitability between aspects of teaching materials. The research purpose is to determine the validity of supplementary teaching materials on buffer solutions that can train argumentation skills. This research is a type of development research that focuses on developing products for learning using the ADDIE model that is limited to the development stage. The instrument used in this research is a validation sheet consisting of content and construct validity. The target of the research is supplementary teaching materials in practicing argumentation skills on buffer solutions. The teaching materials were assessed by 3 validators, that is, experts in chemistry learning. The assessment results from the validation sheet are content validity has a mode of 4 and construct validity has a mode of 4 is declared valid. From this assessment can conclude that the supplementary teaching material on buffer solutions material is valid in supporting argumentation skills training. Based on the results, it is expected to contribute to producing additional teaching materials that are feasible to help train the argumentation skills of students. In addition, the results of this study are also expected to help readers, especially educators, to gain knowledge and references to teaching materials that can be used in training argumentation skills.